Late Neoarchean sanukitoids in the North China Craton: A geodynamic perspective - Guozheng Sun; Shuwen Liu; Lintao Wang; Yang Yu; Shengyao Yu; Huahua Cao; Lei Gao; Yalu Hu; Jinghao Fu (Geosystems and Geoenvironment)
The formation, evolution, and geodynamics of the Archean continent is a hot topic in solid earth science. Sanukitoids are the oldest Mg-Fe-K-rich granitoid magmas recognized so far on Earth, and their crust-mantle interaction process is a golden key to deciphering the formation and evolution of early continental crust. Sanukitoid suites consist of late Archean (3.0–2.5 Ga-old) plutonic rocks ranging from diorites, monzodiorites, and granodiorite, typically with abundant cognate mafic enclaves. Geochemically, they have a mantle signature (high content of Mg, Ni, Cr, and high Mg#) and enrichment in LILE (especially K, Ba, and Sr). It is generally believed that Archean sanukitoids originated from an enriched or metasomatized lithospheric mantle source, and its parental magmas are water-rich and highly oxidized, which is probably genetically related to gold mineralization. Here we compile the geochemical data for late Neoarchean (2.6–2.5 Ga) sanukitoids from the North China Craton and conduct a systematic petrogenetic classification. The less-differentiated sanukitoid magma (SiO2 < 62 wt%) was controlled by multiple factors such as metasomatic component, metasomatic degree, and melting P-T conditions, indicating that near-surface weathering had already existed in the late Archean. The differentiated sanukitoids (SiO2 > 62 wt%) were formed by extensive fractional crystallization of less-differentiated sanukitoid melts, accompanied by crust-mantle magmatic mixing. These late Neoarchean sanukitoids are distributed sporadically throughout the North China Craton without zonation. Combined with other evidence of magmatism, metamorphic deformation, and thermodynamic numerical modeling, we propose that the sanukitoids may develop under the microplate tectonic regime, characterized by small-scale and short-term warm subduction.